Profile and early outcomes of surgical reconstruction of coronary artery atresia in children. (30th August 2021) - Li, Hanmei; Wang, Hailing; Lin, Ye; Rui, Lu; Li, Shoujun
Abstract:  : OBJECTIVES: Coronary artery atresia is a rare coronary artery anomaly in children and has a high rate of misdiagnosis. We aimed to summarize the profile and early outcomes after the surgical reconstruction of coronary artery atresia in children. METHODS: A retrospective analysis was performed in 12 consecutive patients with coronary artery atresia who were admitted to the Department of Paediatric Cardiac Surgery of Fuwai Hospital between October 2016 and September 2020. Ten patients underwent surgical reconstruction of the coronary artery with the pulmonary artery anterior wall, and 8 patients underwent concomitant mitral valvuloplasty. RESULTS: There were 6 females and 6 males, with an age of 1.75 years [interquartile range (IQR), 1.0–3.5] and weight of 10.0 kg (IQR, 8.9–14.75). There were 10 cases of left coronary artery atresia and 2 cases of right coronary artery atresia. All the patients were initially misdiagnosed in the outpatient clinic, but further nonselective coronary angiography confirmed the diagnosis of coronary artery atresia. In all 10 patients with mitral regurgitation, echocardiogram of the mitral valve chordae and papillary muscle revealed ischaemic changes. The clamp time was 89.0 min (IQR, 75.0–101.0), the pump time was 126.0 min (IQR, 119.0–132.0) and the intensive care unit stay time was 1.5 days (IQR, 1.0–3.0). No perioperative deaths were noted. After 9.5 months (IQR, 5.5–13.5) of follow-up, 2 patients with fractional shortening that significantly decreased to 14.1% and 14.8% died and 1 patient had moderate pericardial effusion that improved after treatment with oral diuretics. Coronary artery ultrasound and enhanced computed tomography showed a patent main coronary artery in all the patients. CONCLUSIONS: Coronary artery atresia in children is often associated with mitral regurgitation, and mitral valve chordae and papillary muscle exhibit ischaemic changes. Coronary artery reconstruction is safe and effective in children with coronary artery atresia. Abstract : Coronary artery atresia is a rare disease [1].